The Relationship Between The Weekly Soft Drinks Consumption and Body Mass Index Among Adolescents - Ledyah Meri Liani; Rury Tiara Oktariza; Ertati Suarni (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Soft drink consumption rate among adolescents was the highest and it is accompanied by an increase in the incidence of obesity. This study aimed to analyze the relationship between the frequency and volume of weekly soft drink consumption and body mass index among adolescents. This cross-sectional study involved 78 senior high school students in Palembang. The frequency of soft and energy drink consumption is assessed every week. The body mass index (BMI) was measured by standardized anthropometry. Data was then analyzed computerized with a level of significance of P <0.05. Spearman test results show that there was a significant positive correlation between the frequency and volume of weekly consumption of soft drinks and BMI among adolescents (p < 0.001, r = 0.517; p < 0.001, r = 0.568, respectively). Increased consumption of soft drinks among adolescents will be associated with increased body mass index which leads to overweight and obesity.